Sistem Pendukung Keputusan Fuzzy Mamdani pada Alat Penyiraman Tanaman Otomatis - Munjiat Setiani Asih (Program Studi Sistem Informasi, 2018)
In the gardening activities that cannot be separated from the activities of watering plants. Almost everyone is still doing the activity of watering the plants manually, by watering the plants one by one is time-consuming enough and wasting energy. Watering plants is an activity that is always done every day by almost everyone that has plants at home, office and elsewhere. The activity of watering the plants manually can not know how much water is needed by the plant so that many plants die of excess water. With the development of technology provides ease of watering plants. Technological advances include automatic plant watering, automatic plant watering equipment utilizing micro controller as a circuit brain that processes the entire series to be used for watering plants. Knowledge of fuzzy mamdani can be used as a reference when the plants watered or not to take the value of soil moisture and air temperature, so the need for water plants can be met.Keywords: automatic, air temperature, soil moisture, fuzzy mamdani